Service Quality, Information Technology and Complaint Handling on Customer Satisfaction at BPJS Kesehatan Main Branch Surabaya - Tara Riski Amalia; Elok Damayanti; Hermien Tridayanti; Bayu Airlangga Putra (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2021)
This study aims to see the simultaneous and partial effect of THE EFFECT OF SERVICE QUALITY, INFORMATION TECHNOLOGY AND HANDLING OF COMPLAINTS ON CUSTOMER SATISFACTION AT BPJS KESEHATAN BRANCH SURABAYA this type of research uses a quantitative approach. Collecting data using interviews, observation and questionnaires. The population of this study were customer of BPJS Kesehatan Branch Surabaya with a sample of 45 respondents. The analysis method used is multiple linear regression analysis and using a tool in the form of computer software SPSS program. Based on the T test for the Service Quality variable (X1), it was obtained that T_count = 0.969 while T_table 1.681 had no significant effect on Customer Satisfaction (Y). For the Information Technology variable (X2), T_count = 2,620 while T_table 1. 681 has a significant effect on Customer Satisfaction (Y). For the Complaint Handling variable (X3) obtained T_count = 1.160 while T_table 1.681 then it has no significant effect on Customer Satisfaction (Y). Based on the F test obtained F_count = 8.583 while F_table 2.83 then the regression analysis model is significant. Based on the results of the study, it can be concluded that the variables of Service Quality and Complaint Handling have no partial effect, while the Information Technology variable has a partial effect on Customer Satisfaction. The variables of Service Quality, Information Technology, and Complaint Handling have a significant effect simultaneously on Customer Satisfaction. Based on the F test obtained F_count = 8.583 while F_table 2.83 then the regression analysis model is significant. Based on the results of the study, it can be concluded that the variables of Service Quality and Complaint Handling have no partial effect, while the Information Technology variable has a partial effect on Customer Satisfaction. The variables of Service Quality, Information Technology, and Complaint Handling have a significant effect simultaneously on Customer Satisfaction. Based on the F test obtained F_count = 8.583 while F_table 2.83 then the regression analysis model is significant. Based on the results of the study, it can be concluded that the variables of Service Quality and Complaint Handling have no partial effect, while the Information Technology variable has a partial effect on Customer Satisfaction. The variables of Service Quality, Information Technology, and Complaint Handling have a significant effect simultaneously on Customer Satisfaction.